Energy waste reduction in University of Ibadan, Nigeria’s water factory using energy audit approach (2023)
The technical cost incurred in providing adequate services for drinkable water production and distribution is high in developing countries of which Nigeria is no exception. By analysing the energy aspect of this cost, with a view of eliminating non-value-adding energy wastes, the cost of production can be reduced. In this work, an energy audit of the University of Ibadan water factory has been carried out, as a means of reducing the electrical energy wastes within the factory, as well as the associated costs to these energy wastes. Data on equipment being used and their power ratings were collected via walkthrough audit, by means of interviews and personnel observation, and thereafter inputted into Excel spreadsheet in order to determine the extent of energy consumption of each of the factory equipment, areas of energy wastage and areas of energy conservation opportunities. The factory’s structural data was obtained through the use of a 50m fibre measuring tape, in order to carry out lighting, air-conditioning and ventilation assessments on selected rooms in the factory, as means of proper energy conservation. Energy management measures were deployed by suggestion of more efficient equipment. Major equipment found includes automatic filling machine, pumps, steam generator, conveyor etc. The total electrical energy consumption of the factory was 9,280.899 kWh, of which equipment such as pumps took 20% (highest energy consumption). Areas of major energy consumption include pet blowing room, production room 1, production room 2 and the borehole area. While the current cooling capacities of most rooms in the factory were above the cooling requirement of each room, the luminosity requirement of selected rooms in the factory is surpassed by the current luminosity level found. Energy management measures were found to reduce the energy consumption of the factory by 17%, saving a sum of 87,906.207 naira of electrical energy cost monthly. In conclusion, the energy audit carried out on the University of Ibadan water factory was found useful in reducing energy waste and associated costs within the water factory. This approach can be applied in industries for electricity cost reduction, hence, production cost.